Reinstatement of Dendrobium sinense (Orchidaceae; Dendrobiinae) from D. christyanum with morphological and molecular evidence - Chen, Yu-Ming; Yan, Yin; Huang, Si-Ming; Zhou, Cheng-Yuan; Wang, Mao-Hua; Li, Ming-He (Phytotaxa, 2026)
Dendrobium sinense Tang & F.T.Wang (Orchidaceae) was treated as a synonym of D. christyanum Rchb.f. Critical observations of herbarium materials together with living plants in the wild, however, revealed stable morphological differences between the two taxa. D. sinense differs from D. christyanum by the longer (5.0–21.0 cm vs. 2.0–5.0 cm) and slender (0.3–0.4 cm vs. 0.6–1.0 cm) stems, and the broadly ovate (vs. obliquely rhombic) lateral lobes of labellum. Additionally, the two species exhibit geographically allopatric distributions and distinct, non-overlapping flowering periods. Phylogenetic reconstructions derived from nuclear region ITS and four plastid markers (matK, rbcL, trnH–psbA, and trnL) consistently recover them as separate and well-supported lineages. Consequently, these lines of evidence substantiate the recognition of D. sinense as a distinct species, and its specific status is therefore reinstated.